Odpowiedzi

  • Użytkownik Zadane
2009-09-27T10:04:26+02:00
C) 10 - licz. 3c-1 mian. 2 = licz. 6c+3 mian. 11
10-(3c-1/2)=(6c+3/11) //*22
220-11(3c-1)=2(6c+3)
220-33c+11=12c+6
232-6=12c+33c
45c=226 /:45
c=5 i 1/45

d ) 2- licz. 3a-7 mian. 4 +licz. a+17 mian. 5 = 0
2-(3a-7/4)+(a+17/5)=0 //*20
40-5(3a-7)+4(a+17)=0
40-15a+35+4a+68=0
-11a=-143//:(-11)
a=13

e ) licz. b+6 mian. 2 + licz. 5 -4b mian. 3 = licz 8-b mian. 6
(b+6/2)+(5-4b/3)=(8-b/6) //*6
3(b+6)+2(5-4b)=8-b
3b+18+10-8b=8-b
-5b+b=8-18
-4b=-10//:(-4)
b=2,5

f ) licz. 9c+7-2c mian. 2 +licz. c-2 mian. 7 = 36
(9c+7-2c/2)+(c-2/7)=36 //*14
7(9c+7-2c)+2(c-2)=504
63c+49-14c+2c-4=504
51c=504-45
51c=459//:51
c=9

mam nadzieje, że dobrze przepisałam :)